2016
DOI: 10.1371/journal.pcbi.1005005
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Modeling and Simulation Approach to Investigate Mechanisms of Subcellular cAMP Compartmentation

Abstract: Subcellular compartmentation of the ubiquitous second messenger cAMP has been widely proposed as a mechanism to explain unique receptor-dependent functional responses. How exactly compartmentation is achieved, however, has remained a mystery for more than 40 years. In this study, we developed computational and mathematical models to represent a subcellular sarcomeric space in a cardiac myocyte with varying detail. We then used these models to predict the contributions of various mechanisms that establish subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 60 publications
2
56
0
Order By: Relevance
“…It is also well-known that calcium spikes are necessary for changes in cAMP concentrations, but only certain bursts of calcium spikes increase cAMP levels in neurons [11]. The dynamics of calcium-induced cAMP has been modeled by us and others [15,22,24,46] with a focus on identifying the mechanisms underlying interdependent oscillations. We showed that cAMP is primarily sensitive to the longer timescale effects of calcium rather than the shorter time scales [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well-known that calcium spikes are necessary for changes in cAMP concentrations, but only certain bursts of calcium spikes increase cAMP levels in neurons [11]. The dynamics of calcium-induced cAMP has been modeled by us and others [15,22,24,46] with a focus on identifying the mechanisms underlying interdependent oscillations. We showed that cAMP is primarily sensitive to the longer timescale effects of calcium rather than the shorter time scales [15].…”
Section: Discussionmentioning
confidence: 99%
“…The head shape, neck length, and neck diameter in spines can change during the synaptic plasticity [21]; changes in spine morphology and spine density are associated with learning and memory [21]. In other cell types, it is well-known that the spatial localization of cAMP regulating molecules and spatial aspects of signaling can govern its dynamics [22,23]. Two key types of enzymes that produce and degrade cAMP are believed to be responsible for cAMP subcellular compartmentalization.…”
Section: Introductionmentioning
confidence: 99%
“…To decode how these two quantities affect the spatiotemporal dynamics of C, we conducted the following simulations -(i) spine apparatus size was varied by changing ρ; we used three different values of ρ (0.1, 0.5, and 0.9) to capture the extreme volume changes due to small, medium, and large spine apparatus. (ii) The diffusion constant of C was varied to capture the range of intracellular diffusion from a crowded regime to free diffusion (1, 10, 100 µm 2 /s) [70][71][72][73][74][75][76]. We found that with small spine apparatus (ρ = 0.1), a significant concentration gradient exists in the radial direction when the diffusion coefficient is small (D = 1µm 2 /s) at early time points but not for larger diffusion coefficients (Figure 4a).…”
Section: Combined Effect Of Spine Apparatus Size and Diffusion Coeffimentioning
confidence: 96%
“…Although our system does show the ability to oscillate in and out of phase in a well-behaved manner, this will not produce our desired form if a homogenous boundary is present. Previous studies have looked at spatial gradients in the context of cAMP and PKA and found out that a localization must occur for the system to form one (Yang et al 2016). Therefore, when moving to a 3D spatial map, we must consider how two solution regimes can be recovered.…”
Section: Model Developmentmentioning
confidence: 99%